Role of Transesophageal Echocardiography in Guiding and Evaluating Left Atrial Appendage Occlusion in Patients With Non‐Organic Heart Disease - Xiaoli Long; Xiaohu Guo; Jiwen Xie; Xiaoyong Fan; Dongxia Yang; Xiaoting Mao; Jing Xie (Annals of Noninvasive Electrocardiology)
ABSTRACT Objective To assess the guiding role of transesophageal echocardiography (TEE) intraoperatively and its evaluative function postoperatively during left atrial appendage occlusion (LAAO) in patients with non‐organic heart disease (NOHD). Methods In this retrospective observational study, a total of 48 patients with NOHD who underwent LAAO in the Department of Cardiology at The First People's Hospital of Lanzhou City from April 2020 to September 2022 were recruited. TEE findings during and after the procedure, cardiac chamber size, and cardiac function parameters at different surgical stages, postoperative occlusion efficacy, and complications were recorded. The application value of TEE in LAAO for patients with NOHD was evaluated. Results Comparative analysis TEE‐measured the maximum diameter of the LAAO (22.37 ± 3.86 mm) was significantly smaller than X‐ray angiographic measurement (23.45 ± 4.22 mm; p < 0.05). One month after radiofrequency ablation, TTE revealed a statistically significant reduction in left atrial diameter (p < 0.05). Four cases (8%) exhibited minor peri‐device leak (< 3 mm), and no major complications occurred. Conclusion TEE shows significant application value for monitoring anatomical changes, guiding device sizing, and detecting peri‐device leaks during and after LAAO for patients with NOHD.